A family of 3d metal clusters based on N–N single bonds bridged quasi-linear trinuclear cores: the Mn analogue displaying single-molecule magnet behavior. Issue 12 (7th February 2018) - Wang, Kai; Tang, Shen; Hu, Zhao-Bo; Zou, Hua-Hong; Wang, Xiao-Lu; Li, Yan; Zhang, Shu-Hua; Chen, Zi-Lu; Liang, Fu-Pei
Abstract : A family of 3d metal clusters featuring N–N single bonds bridged quasi-linear trinuclear cores were designed and synthesized. The Mn analogue represents a very rare case of quasi-linear 3d SMM using N–N single bonds as magnetic coupling pathways. Abstract : The reactions of the diacylhydrazine ligands N, N ′-bisalicyl-2, 6-pyridine dicarbohydrazide (H6 sphz) and N, N ′-bis(3-methoxysalicyl)-2, 6-pyridine dicarbohydrazide (H6 msphz) with various 3d metal salts, afforded a series of coordination clusters, namely, [MnIII2Mn II (sphz)(acac)2 (CH3 OH)4 ] (1, acac − = acetylacetone anions), [NiII3(msphz)(Py)4 ] (2, Py = pyridine), [CuII6(sphz)2 (Py)4 ] (3 ) and [CuII6(msphz)2 (Py)4 ]·2DMF·2H2 O (4 ). Cluster1 and2 are single ligand assembled quasi-linear trinuclear structures. Both3 and4 consist a pair of quasi-linear Cu3 cores, which are linked together by two crossed ligands. The adjacent 3d metal ions in all trinuclear cores of1–4 are bridged by N–N single bonds of ligands, which convey ferromagnetic (FM) interactions between 3d metal centers of1, and antiferromagnetic (AFM) interactions between those of2–4 . In particular, the FM interactions and linear arrangement of mixed-valence Mn centers in1 result in a large spin ground states value ( S T ) of 13/2, as well as single-molecule magnet (SMM) behavior of slow relaxation and hysteresis of magnetization.